Analisis Pengalaman Pengguna pada Aplikasi Mandatory Pedulilindungi berbasis Android menggunakan Metode UX Curve - Wahyu Nur Arifin; Hanifah Muslimah Az-Zahra; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Coronavirus (COVID-19) has become global health problem that entered Indonesia since March 2020. This is an infectious disease caused by SARS-CoV-2. The government through the Indonesian Ministry of Health released PeduliLindungi application as an effort to deal with COVID-19. In the early stage PeduliLindungi tend to be voluntary application, but after being regulated through the Minister of Domestic Affairs Instruction Number 38 and 40 of 2021 which regulates community activities restrictions enforcement in Indonesia, PeduliLindungi became mandatory for Indonesian. This study aims to determine the long-term experience of users in using mandatory Android-based PeduliLindungi application, whether the user experience at the beginning who is forced to use the application can change for the better. Respondents involved in this study were 12 people. Each respondent will be asked to draw the 5 dimensions of the UX Curve, there are general UX, attractiveness, ease of use, utility and degree of usage. This study produced 60 curves from 12 respondents. At the end of the research, user experience did increasing with 45 out of 60 curves showing an improving trend, but 8 out of 12 respondents had not shown an impression of liking and recommend the use of the application to others.